Zooplankton excretion metabolites stimulate Southern Ocean phytoplankton growth - Coello-Camba, A; Llabres, M; Duarte, Carlos M.; Agusti, Susana (Polar Biology, 2017)
Source at https://doi.org/10.1007/s00300-017-2123-2 . Warming over Antarctica is leading to changes in the zooplankton communities inhabiting the Southern Ocean. It has been observed that zooplankton not only regulates phytoplankton through grazing, but also through the recycling of nutrients that are essential for phytoplankton growth. In this way, the effects of warming on zooplankton populations will change the amount or proportion at which recycled nutrients are restored. To estimate how the recycled nutrients released by zooplankton populations, dominated by krill (Euphausia superba), amphipods or copepods, affect the phytoplankton uptake and communities, we performed four incubation experiments: two close to the Antarctic Peninsula and two at the Southern Atlantic Ocean. Our results showed a stimulating effect of the addition of metabolites on ammonia removal rates and on the net growth of phytoplankton communities, with different responses amongst the different phytoplankton groups. According to our results, phytoplankton net growth and community composition may be altered if this relevant source of nutrients is lost due to projected changes in the abundance or distribution of these zooplankton populations.